Tinjauan Yuridis Hukum Perlindungan Anak terhadap Pelaku Kejahatan Seksual terhadap Anak di Indonesia (SETARA : Jurnal Ilmu Hukum, 2023)
This article examines the regulation and application of chemical castration sanctions against perpetrators of sexual crimes against children in Indonesia. The issue is important because the government has attempted to respond to the persistence of child sexual violence through stricter punishment, yet the introduction of chemical castration has generated ethical, medical, and human rights controversy. Using normative and empirical juridical research, the article reviews statutory changes in child protection law, Government Regulation Number 70 of 2020, and the early judicial application of chemical castration. The study finds that chemical castration was introduced as an aggravated measure intended to produce deterrence, prevent repetition, and accompany rehabilitation for offenders in certain categories of child sexual violence. At the same time, the sanction continues to face criticism concerning bodily integrity, the role of medical professionals, and compatibility with constitutional and human rights norms. The article concludes that the implementation of chemical castration requires strict clinical assessment, clear procedural safeguards, and careful limitation to cases that meet the legal requirements, while the protection of child victims must remain the primary concern.
Keywords: Chemical Castration; Sexual Crimes Against Children; Child Protection; Criminal Sanctions; Human Rights